Using No‐Stakes Educational Testing to Mitigate Summer Learning Loss: A Pilot Study. Issue 2 (15th September 2014) - Zaromb, Franklin; Adler, Rachel M.; Bruce, Kelly; Attali, Yigal; Rock, JoAnn
Abstract : This study investigates the benefits of no‐stakes educational testing during students' summer vacation as a strategy to mitigate summer learning loss. Fifty‐one students in Grades 3–8 from the Every Child Valued (ECV) and Lawrence Community Center (LCC) summer programs in Lawrenceville, NJ, took short, online assessments throughout the summer, covering knowledge and procedural skills in both mathematics and reading that they had previously learned. Students were randomly assigned to mathematics or reading conditions, whereby over the course of 5 weeks, students in the mathematics condition took online assessments in mathematics fluency two or three times per week and students in the reading condition took online assessments in reading components skills (word recognition and decoding, vocabulary, morphological awareness, and reading comprehension) two or three times per week. All students completed tests in both math and reading components at the beginning and end of the summer in order to compare baseline and final performance. Although students did not show significant summer learning loss in either reading components or mathematics fluency, students in the reading condition scored significantly higher, on average, on standardized tests of reading components administered at the end of the study than students in the mathematics condition. Given the small sample size and variations in grade level, academic subjects, computer programs, and testing conditions, it is premature to draw any firm conclusions from these findings. Abstract : Report Number: ETS RR–14–21